IMPACT OF STRATEGIC MANAGEMENT ACCOUNTING ON FIRM’S FINANCIAL PERFORMANCE: EVIDENCE FROM BANGLADESH’S MANUFACTURING SECTOR - Begum , Fahmida; Rahman, Md. Musfiqur (International Journal of Accounting & Finance Review, 2026)
Manufacturing firms in Bangladesh operate in an increasingly competitive and dynamic business environment where effective strategic decision-making is essential for sustaining financial performance. Despite the growing importance of Strategic Management Accounting (SMA), empirical evidence on its adoption and influence on financial performance in the Bangladeshi manufacturing sector remains limited. This study examines the extent of SMA adoption and investigates the relationship between SMA practices and the financial performance of manufacturing companies in Bangladesh. The study employs a quantitative research design based on contingency theory. It uses primary data collected through a structured questionnaire survey of 78 listed manufacturing companies selected through stratified random sampling from the Dhaka Stock Exchange. Data were collected between August and November 2023 and analyzed using multivariate regression and Structural Equation Modelling (SEM). The analysis considers five contingent factors influencing SMA adoption: firm size, company age, ownership participation, accounting staff qualifications, and technology usage. The results reveal that ownership participation (β = 0.421, p < 0.01) and technology usage (β = 0.289, p < 0.01) have significant positive effects on SMA adoption, while accounting staff qualifications show a negative association (β = –0.159, p < 0.10). Firm size (β = 0.117) and company age (β = 0.103) demonstrate positive but statistically insignificant relationships with SMA usage. Furthermore, SEM results indicate that strategic analysis significantly and positively affects financial performance (β = 0.30). The findings suggest that SMA adoption is positively influenced by ownership involvement and technological capability and that greater use of SMA practices contributes to improved financial performance among manufacturing firms in Bangladesh. JEL Classification Codes: M11, M40, M41.